THE STUDY OF FREEDOM OF MOVEMENT OF LIMBS AND RESTRICTIVE CONSEQUENCES AS A RESULT OF INJURY (American Journal of Interdisciplinary Research and Development, 2022)
Disappointing statistics claim that from 20 to 30% of ambulance calls are due to injuries. In fact, more than 10 thousand people annually seek medical help only after workplace accidents. We tell you more about the types of injuries and the classification of injuries in the article. In this article, we can discuss about the study of the freedom of movement of limbs and the restrictive consequences as a result of injury.